Zeta Potential Change and curing effects on Shield Muck solidified by Metal Ion Complex Catalysis - Bosong Ding; Ping Lou; Isamu Yoshitake; Rui Wang; Zhenyu Wang; You Wang (Scientific Reports)
Abstract Using potentiometric testing, we investigated the zeta potential of shield muck curing materials’ particle surfaces, varying the concentration of metal ion complex. We analyzed the microscopic characteristics of shield muck curing products by using the electron microscopy, revealing the impact of metal ion complex on curing. Results showed that the metal ion complex significantly reduces the surface zeta potential of shield muck and conventional curing materials, with cement showing the most substantial effect, followed by shield muck, calcium carbonate, and calcium sulfate. The concentration of metal ion complex negatively correlates with the zeta potential within a range of 0 to 100 mmol/L. Comparing shield muck cured for 7 and 28 days, with and without metal ion complexes, indicated that metal ion complexes accelerate crystalline product formation, increasing the compressive strength of shield cinder cured products by over 35%. Fitted curves and empirical parameter equations of zeta potential and metal ion complex concentration align with experimental results. This study provides a reference for the efficient treatment and sustainable utilization of shield slag soil, holding significant practical engineering value.